The relationship of PrEP beliefs to perceived personal, interpersonal and structural benefits and barriers to PrEP use in women who inject drugs - Kirsten Paulus; Patrick J.A. Kelly; Jesse Brajuha; Paul D'Avanzo; Emily F. Dauria; Aurora Trainor; Annabelle Alrez; Sarah Bauerle Bass (BMC, 2023)
Abstract Background Women who inject drugs (WWID) have significant biological, behavioral, and gender-based barriers to accessing HIV prevention services, including Pre-Exposure Prophylaxis (PrEP) medication. Little is known about how beliefs about PrEP impact both perceived barriers and benefits of PrEP use and how they may be related to the decision-making process. Methods Surveys were conducted with 100 female clients of a large syringe services program in Philadelphia, Pennsylvania. The sample was categorized into three groups based on mean PrEP beliefs scores using terciles: accurate beliefs, moderately accurate beliefs, and inaccurate beliefs. Oneway ANOVA tests were used to compare groups by perceived benefits and barriers to PrEP, drug use stigma, healthcare beliefs, patient self-advocacy, and intention to use PrEP. Results Participants had a mean age of 39 years (SD 9.00), 66% reported being White, 74% finished high school, and 80% reported having been homeless within the past 6 months. Those with the most accurate PrEP beliefs reported highest intent to use PrEP and were more likely to agree that benefits of PrEP included it preventing HIV and helping them "feel in charge". Those with inaccurate beliefs were more likely to strongly agree that barriers, such as fear of reprisal from a partner, potential theft, or feeling they "might get HIV anyway", were reasons not to use PrEP. Conclusions Results indicate perceived personal, interpersonal and structural barriers to PrEP use are associated with accuracy of beliefs is, pointing to important intervention targets to increase uptake among WWID.